KONSEP RUANG DALAM BAHASA DAN PEMIKIRAN MENERUSI PANTUN MELAYU - Mohamad Nor, Noor Hasnoor; Mat Hussain, Eizah (JURNAL MELAYU SEDUNIA, 2020)
Space basically refers to the empty part or open section of some thing or place. The concept of space in Malay is closely related to language and thought of the community. Either physically or metaphorically, the concept of space in the Malay pantun is very significant as it is a medium of communication that the Malays have often used to express their mind and emotion in a more polite manner relating to the culture of the Malays. The space aspect in this research was examined regarding the correlation between pantun, language and thought of Malay speakers using the corpus. The Karya Agung Pantun Melayu (2001) text, that contained the selected corpus from the fieldwork and the compilation of old manuscript that was highlighted as the Malay Masterpiece are used as a corpus. The corpus is a computer-aided processed by using antconc 3.4w software via concordance techniques. Analysis of the study was based on semantic field of Malay speakers’ worldview pertaining physical, psychological and cultural space. The results of this study, in addition to showing the area in terms of language and thought reform also prove that Malay poem picture of Malay language and thought related local wisdom in human civilization.